The pandemic and the feminisation of the Church? How male and female churchgoers experienced the Church of England's response to Covid-19. Issue 2 (3rd April 2022) - Francis, Leslie J.; Village, Andrew
ABSTRACT: The Church of England responded quickly and decisively to the Government's lockdown of the nation on 23 March 2020 by a total lock-up of all its churches and a swift move to a new online presence. Drawing on data from the Coronavirus, Church & You Survey provided by 1, 642 female and 854 male churchgoing lay Anglicans in England, the present analyses tested the thesis that the response of the Church of England would be assessed more favourably by women than by men. The data found that men evaluated the national leadership less favourably, were more critical of the policy to lock-up churches, and were less positive about the online future. These findings are read against the background of a Church in which men are already marginalised and may have become more so as a consequence of the pandemic.